A wavefront division multiplexing holographic scheme and its application in looking through diffuser - Chen L.; Kumar Singh R.; Vinu R.V.; Chen Z.; Pu J. (My University, 2025)
We present a spatial light modulator (SLM) assisted compact holographic method and illustrate its application by imaging through a random scattering medium. The merit of the proposed method is wavefront division multiplexing, i.e. the dual wavefront modulations over a single SLM. Two different wavefront shapes: a reference-light shape and a phase object, are combined over the SLM. One advantage of this scheme is the flexible modulation of the reference light. The experimental implementation of this method is demonstrated by quantitatively reconstructing different phase objects from the randomly scattered light. This new scheme greatly simplifies the experimental configuration and presents a better stability even in presence of external vibrations, opening avenues for the holography-based scattering imaging application. © 2021 The Author(s). Published by IOP Publishing Ltd on behalf of the Institute of Physics and Deutsche Physikalische Gesellschaft.